2016
DOI: 10.1590/0037-8682-0288-2015
|View full text |Cite
|
Sign up to set email alerts
|

Neurobrucellosis and venous sinus thrombosis: an uncommon association

Abstract: Brucellosis is a commonly diagnosed zoonosis and neurological involvement is rare. A 30-year-old woman presented with a pulsatile headache that was exacerbated by the Valsalva maneuver and refractory to analgesic therapy. The patient also had nausea, cough, and coryza that evolved over 7 days. The neurological examination was unremarkable. Thrombosis of the lateral and sigmoid sinus and ipsilateral internal jugular vein were diagnosed and anticoagulation therapy was started. Brucella spp was identified in a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…In 1999, Zaidan and Al Tahan published the first case of CVST secondary to neurobrucellosis after the patient presented with signs and symptoms of meningitis [7]. Since then, six more articles have been published describing patients with the same diagnosis [3,4,[8][9][10][11]. CVST caused by neurobrucellosis is a rare presentation with good outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1999, Zaidan and Al Tahan published the first case of CVST secondary to neurobrucellosis after the patient presented with signs and symptoms of meningitis [7]. Since then, six more articles have been published describing patients with the same diagnosis [3,4,[8][9][10][11]. CVST caused by neurobrucellosis is a rare presentation with good outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis is a multisystemic disease that has broad clinical manifestations. Clinical presentations can range from asymptomatic to severe illness depending on the organ involved [ 3 ]. The main clinical features of brucellosis include undulant fever, fatigue, weakness, myalgia, and arthralgia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lima et al reported a 30-year-old woman who was presented with thrombosis of the lateral and sigmoid sinus and ipsilateral internal jugular vein. 10 Brucella spp. was identified in the CSF sample by a polymerase chain reaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, blood cultures are positive in only 16 to 30% of patients with neurobrucellosis, and CSF cultures are positive in less than 50% cases. 10 Brucella microagglutination test is also advised by the Centers for Disease Control and Prevention. CSF Coombs' test agglutination with a cut-off titer 1:8 was found to have a high sensitivity and specificity (0.94 and 0.96, respectively) in neurobrucellosis.…”
Section: Discussionmentioning
confidence: 99%